Sentimen Komunitas Driver Ojek Online (Grab) Team Garuda District Kota Pekanbaru - Nelfianti, Aprini; Sidiq, Rd. Siti Sofro (Jurnal Ilmiah Wahana Pendidikan, 2024)
The Team Garuda District community is one of the many online motorcycle taxi communities in Pekanbaru City. This community was formed with the aim of uniting Grab online motorcycle taxi drivers in Pekanbaru City and a sense of close family between fellow professions. The purpose of this study was to determine the form of sentiment of the online motorcycle taxi driver community (Grab) Team Garuda District Pekanbaru City and the implications of community sentiment in supporting its members' online motorcycle taxi businesses using Emile Durkheim's social solidarity theory. This study uses a qualitative research method with data collection through observation, interview, and documentation techniques. The results of the study show that first, the form of sentiment of the online motorcycle taxi driver community is feeling the same, suffering the same, and needing each other. This community sentiment causes the formation of social solidarity in the community. Solidarity in this community is mechanical solidarity and there are also organic elements. Second, the implications of the sentiment of the online motorcycle taxi driver community for its members' businesses are 3, namely improving service quality, increasing income, and improving skills.